Evaluation of lignosus rhinocerus aqueous extract on muscarinic receptor in isolated trachea of sprangue-dawley rats - Taha, Syed Muhamad Asyraf Syed (2019)
Asthma is a serious public health concern. There is an increase of asthma cases worldwide and it ranks among the top ten most common chronic disease in the world. Lignosus rhinocerus (Tiger milk mushroom) has been traditionally used in treatment of asthma. Therefore, it is important to elucidate the receptor involved for this extract on airway hyperresponsiveness and evaluate its roles in the mechanism of airway smooth muscle relaxation. The main objective of the study was to evaluate the effect of L. rhinocerus aqueous extract (LRE) on the muscarinic receptor functions in isolated trachea of Sprague Dawley rats. LRE was prepared using hot soxhlet extraction process and it was freeze-dried. Isolated rat trachea ring was used in functional myograph study to evaluate the relaxation effect of LRE in comparison to non-selective muscarinic antagonist, atropine on carbachol-induced contractile (non-selective muscarinic agonist) tone. The LRE produced more than >50% relaxation effect at 30 mg/ml in 3 μM carbachol-induced contraction with pIC50 1.62 ± 0.01. Atropine produced complete relaxation at 9 nM with pIC50 of 5.71 ± 0.05. In conclusion, this study suggests that the LRE induced relaxation in trachea smooth muscle was mediated by antagonistic effect on muscarinic receptor of cholinergic system.